2008
DOI: 10.1002/path.2353
|View full text |Cite
|
Sign up to set email alerts
|

Loss of heterozygosity at 9q32–33 (DBC1 locus) in primary non‐invasive papillary urothelial neoplasm of low malignant potential and low‐grade urothelial carcinoma of the bladder and their associated normal urothelium

Abstract: Tumour recurrence has a major impact on patients with non-invasive papillary urothelial tumours of the bladder. To explore the role of DBC1 (deleted in bladder cancer 1 locus), a candidate tumour suppressor gene located at 9q32-33, as prognostic marker we have performed loss of heterozygosity (LOH) testing in 49 patients with primary papillary urothelial tumours and associated normal urothelium. Data from the 38 tumours and 11 specimens of normal urothelium that were informative in the LOH study (D9S195 marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 45 publications
1
13
0
1
Order By: Relevance
“…9,12 Most recently, Lopez-Beltran et al could show that the deletion of the DBC1 (deleted in bladder cancer 1) locus on 9q32-33 in normal urothelium seemed to be frequent and influenced the prognosis of noninvasive papillary bladder cancer by selecting cases with an increased proliferation. 17 These findings of a frequent chromosomal alteration on chromosome 9q fit well with our own results from a LOH study on normal urothelium in cystectomy specimens showing the most frequent deletions in microsatellite marker D9S1113 located on chromosome 9q33.3-34.1 which is in close proximity to DBC1.…”
supporting
confidence: 89%
“…9,12 Most recently, Lopez-Beltran et al could show that the deletion of the DBC1 (deleted in bladder cancer 1) locus on 9q32-33 in normal urothelium seemed to be frequent and influenced the prognosis of noninvasive papillary bladder cancer by selecting cases with an increased proliferation. 17 These findings of a frequent chromosomal alteration on chromosome 9q fit well with our own results from a LOH study on normal urothelium in cystectomy specimens showing the most frequent deletions in microsatellite marker D9S1113 located on chromosome 9q33.3-34.1 which is in close proximity to DBC1.…”
supporting
confidence: 89%
“…- (CGH) has to be performed. CGH results from our present study, and those of others, found that frequent chromosome losses are on 3p, 4p, 6q, 9p, 9q, 8p, 11p, 13q, 17p, and 18q while chromosomes gains are on 1q, 3q, 5p, 6p, 7p, 8q, 10q, 11q, 13q, 17q, 20q (12,19,20,(25)(26)(27)(28)(29)(30). As a result, the high frequency of allelic imbalance of chromosome 1q, 10q, and 11q, detected in this study was probably due to chromosomal gain.…”
Section: Discussionmentioning
confidence: 57%
“…The third wave of genetic alterations occurs when the fully transformed phenotype of carcinoma in situ is apparent. Similarly, Lopez-Beltran et al [55] recently demonstrated MACC with LOH at 9q32-33 DBC1 (deleted in bladder cancer 1) in normal urothelium from patients with low-grade papillary urothelial tumors. The most striking observation in their study was the association between DBC1 locus in normal urothelium with tumor recurrence and progression [55].…”
Section: Molecular Alterations In Flat Lesionsmentioning
confidence: 92%
“…Similarly, Lopez-Beltran et al [55] recently demonstrated MACC with LOH at 9q32-33 DBC1 (deleted in bladder cancer 1) in normal urothelium from patients with low-grade papillary urothelial tumors. The most striking observation in their study was the association between DBC1 locus in normal urothelium with tumor recurrence and progression [55]. Of the 38 lowgrade stage Ta papillary urothelial carcinomas and associated samples of 11 normal urothelium specimens, which were informative in their 9q32-33 LOH study, 12 (31.6%) showed tumor recurrence and 5 (13.1%) showed tumor stage progression when there was deletion of DBC1.…”
Section: Molecular Alterations In Flat Lesionsmentioning
confidence: 92%